The Healthy Context Paradox Between Bullying and Emotional Adaptation: A Moderated Mediating Effect - Pu J; Gan X; Pu Z; Jin X; Zhu X; Wei C (Psychology Research and Behavior Management, 2024)
Junwei Pu,1 Xiong Gan,1 Zaiming Pu,2 Xin Jin,1 Xiaowei Zhu,1 Chunxia Wei3 1College of Education and Sports Sciences, Yangtze University, Jingzhou City, Hubei Province, People’s Republic of China; 2College of Marxism, ENSHI POLYTECHNIC, Enshi City, Hubei Province, People’s Republic of China; 3Foreign languages college, Jingzhou University, Jingzhou City, Hubei Province, People’s Republic of ChinaCorrespondence: Xiong Gan, Department of Psychology, College of Education and Sports Sciences, Yangtze University, Jingzhou, 434023, People’s Republic of China, Tel +86 7168062663, Email 307180052@qq.com Chunxia Wei, Foreign languages college, Jingzhou University, Jingzhou, 434023, Hubei, People’s Republic of China, Email msvivien2023@126.comIntroduction: Bullying is a significant concern for young people, with studies consistently showing a link between bullying and negative emotional consequences. However, the mechanisms that underlie this association remain unclear, particularly in terms of the classroom environment. This study aimed to explore the paradoxical phenomenon between bullying victimization and emotional adaptation among junior high school students in China, using the hypothesis of the healthy context paradox.Methods: The study involved 880 students (565 girls; Mage=14.69; SD=1.407 years), and data were collected using self-reported surveys. The findings of the study, utilizing multilevel structural equation modeling (MSEM) techniques, demonstrated a cross-level moderated effect of classroom-level bullying victimization on the relationship between individual bullying victimization and emotional adaptation.Results: Specifically, the results indicated that in classrooms with higher levels of victimization, the association between individual bullying victimization and increased depressive symptoms and State&Trait anxiety was more pronounced. These findings support the “Healthy context paradox” hypothesis in the Chinese context and provide insight into the mechanisms underlying this phenomenon.Discussion: The results suggest that the classroom environment plays a crucial role in shaping the emotional consequences of bullying and that addressing classroom victimization is crucial for promoting emotional health among young people. By understanding the mechanisms that underlie the association between bullying and emotional consequences, interventions can be developed to target the underlying factors that contribute to this paradoxical phenomenon. Overall, the study provides new insights into the complex relationship between bullying and emotional health among young people, highlighting the importance of considering the classroom environment in addressing this issue.Keywords: the healthy context paradox, bullying victimization, emotional adaptation, the level of classroom victimization